COMMUNICATION STRATEGIES USED IN THE INTERACTION BETWEEN TOURIST GUIDES AND FOREIGN TOURISTS IN BOROBUDUR TEMPLE - Fauziyah, Ida (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2012)
Generally speaking, communication is an inseparable part in daily life since it attempts to convey messages from one person to others. However, there are many problems which occur during the conversation in all languages including English. Therefore, the speakers have to employ some methods in dealing with this kind of problems. Those methods are called communication strategies. More importantly, the communication strategies would be very essential for the speakers who have different knowledge of culture and language. For example, the interaction between foreign tourists and the tour guides. For this reason, I conducted this study which aims to describe how the communication strategies are used in the interaction between the tourist guides and foreign tourists in Borobudur temple. In this study, Celce-Murcia et al’s (1995) model of communication strategies is considered as the most complete and detailed. She divided communication strategies into five main categories. They are avoidance, achievement, stalling, self-monitoring strategies, and interactional strategies. The primary data of this research was in the form of words, sentences, and attitude of the speakers. They were presented in a transcript for each conversation. There were four tourist guides being my research subjects, therefore, there were four transcripts of conversation used as the data. In addition, this research was conducted through qualitative approach since it aims to describe the communication strategies in the conversation. From the analysis of four recorded conversation done by a total of 15 speakers I found out that almost all strategies proposed by Celce-Murcia et al (1995) were employed by the speakers in their conversation in order to compensate for communication breakdowns, except retrieval. From the percentage of the findings, I can conclude that the most used strategy was stalling or time gaining which uses fillers as it has a 21.94% percentage compared to the total amount of the strategies used in the four recorded conversation. After conducting this research, I agree that a real conversation does not always go as smoothly as we think. There are several problems that occur during the communication. In conclusion, the mastery of communication strategy, therefore, is really necessary for the guides in order to cope with those difficulties.